Role and Responsibilities of Notaries in Mining Sector Contracts: In Formal Authority and Accountability and Impact on the Environment - Jatmiko, Sri Wahyu; Siswanto, Robert (Journal of Law, Politic and Humanities, 2025)
This paper examines the ambiguity of notary responsibilities in making mining sector contracts that have an impact on the environment. Through a normative legal approach, it is found that there is a gap and disharmony between notary law and environmental law and the mining sector. Notaries have a central role in the legalization of documents, but without formal obligations regarding the substance of contracts that contain ecological risks, the potential for violations of the precautionary principle increases. This study recommends the reformulation of legal norms and the improvement of ethical guidelines to clarify the accountability of the notary profession in cross-sector transactions